Clustered intracellular Salmonella Typhimurium Blocks Host Cell Cytokinesis - Santos,AJM; Durkin,C; Helaine,S; Boucrot,E; Holden,DW (Infection and Immunity, 2016)
Several bacterial pathogens and viruses interfere with the cell cycle of their host cells to enhance virulence. This is especially apparent in bacteria that colonise the gut epithelium, where inhibition of the cell cycle of infected cells enhances the intestinal colonisation. We found that intracellular Salmonella enterica Typhimurium induced the binucleation of a large proportion of epithelial cells by 14 hours post invasion, which was dependent on an intact Salmonella pathogenicity island-2 (SPI-2) type 3 secretion system. The SPI-2 effectors SseF and SseG were required to induce binucleation. SseF and SseG are known to maintain microcolonies of Salmonella-containing vacuoles close to the microtubule organising centre of infected epithelial cells. During host cell division these clustered microcolonies prevented the correct localisation of members of the chromosomal passenger complex and mitotic kinesin-like protein 1, and consequently prevented cytokinesis. Tetraploidy, arising from a cytokinesis defect, is known to have a deleterious effect on subsequent cell divisions, either resulting in chromosomal instabilities or cell cycle arrest. In infected mice, proliferation of small intestinal epithelial cells was compromised in an SseF/SseG-dependent manner, suggesting that cytokinesis failure caused by S. Typhimurium delays epithelial cell turnover in the intestine.